Democratic Institutions Without Democratic Content?-New Regionalism and Democratic Backsliding in Regional Reforms in Sweden - Johansson, Jörgen; Rönnblom, Malin; Öjehag-Pettersson, Andreas (Frontiers in Political Science, 2021)
The aim of this article is to examine trends of democratic backsliding associated with the long standing reform work on regional institutions and policies in Sweden. To this end, democratic backsliding is conceptualized in a different manner compared to conventional understandings. By doing so, the article highlights a missing aspect in the research on democratic backsliding that concerns how well-intended reforms designed to strengthen democratic institutions can also harbor non-democratic consequences. In Sweden, a new political arena was created when the former county councils were transformed into so-called called regions in 2019. As part of this, the regions have been assigned responsibility for both health care and regional development planning. The overall research problem to be analyzed in this article focuses on the relations between the policy objectives for democracy and regionalist ideas of economic growth that both were central concerns in the reform processes. The results highlight how the governing rationalities in the regional reform processes have changed during the period between 1990 and 2020. The original conception of creating a mini-version of a liberal and representative democracy have turned into a form of democratic backsliding privileging economic goals. The economic rationalities that permeate the political sphere today close the space for articulated different interests and opinions-a dimension that we argue is crucial for any democratic society. We draw two main conclusions: First that the neoliberal aspect of governing is missing in the analysis of democracy at the regional level, resulting in a descriptive discussion of democracy that tend to ignore the effects of the particularly strong emphasis on economic growth. Secondly, that there is a lack of a discussion on democracy that takes the regional level into account, i.e., that the sub-national level should be regarded and thus discussed as a distinctive level of democracy.